2020
DOI: 10.1177/0033354920930133
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Health Effects and Access to Health Care Among Houston Area Residents After Hurricane Harvey

Abstract: Objectives Although research shows that public health is substantially affected during and after disasters, few studies have examined the health effects of Hurricane Harvey, which made landfall on the Texas coast in August 2017. We assessed disparities in physical health, mental health, and health care access after Hurricane Harvey among residents of the Houston–The Woodlands–Sugar Land, Texas, metropolitan statistical area (ie, Houston MSA). Methods We used structured survey data collected through telephone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Race was assessed because of prior research indicating racial and ethnic variations in both health care utilization and disaster exposure. 22 , 23 , 24 , 25 , 26 , 27 VHA priority is assigned on the basis of military service, disability rating, income level, and other factors. Veterans are categorized as low income if they do not have a service-related disability and have income below a VA-determined adjusted income limit (based on resident zip code) or are eligible for Medicaid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Race was assessed because of prior research indicating racial and ethnic variations in both health care utilization and disaster exposure. 22 , 23 , 24 , 25 , 26 , 27 VHA priority is assigned on the basis of military service, disability rating, income level, and other factors. Veterans are categorized as low income if they do not have a service-related disability and have income below a VA-determined adjusted income limit (based on resident zip code) or are eligible for Medicaid.…”
Section: Methodsmentioning
confidence: 99%
“… 15 , 20 , 21 Differences in exposure to flooding after hurricanes also break down along race and ethnicity and socioeconomic status: low-income and racial and ethnic minority populations often experience more flooding than do White and wealthy populations, as has been observed following Hurricanes Katrina, Sandy, and Harvey, because of historical and current structural inequities. 22 , 23 , 24 , 25 , 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…61 Harvey-related job loss also doubled individuals' odds of having PTS. 62 Households that reported economic instability (i.e., loss of a job or income due to Harvey) experienced greater odds of food insecurity post-Harvey compared with households that reported economic stability. 63 Response Black and Hispanic households in Greater Houston experienced disproportionately greater unmet needs during and after Harvey (e.g., inadequate place to sleep, lack of electricity or transportation) relative to White households.…”
Section: Health Impactsmentioning
confidence: 98%
“…Being non-Hispanic Black (vs. non-Hispanic White) was associated with four times the odds of having post-traumatic stress (PTS) after Harvey among a random sample of Greater Houston residents, but the study found no racial/ethnic disparities in physical health impacts. 55 A study of a broader sample of Texans directly threatened by Harvey found no racial/ethnic disparities in mental health. 56 Another study relying on a small convenience sample to examine mental health also found no evidence of disparities.…”
Section: Health Impactsmentioning
confidence: 99%
“…55 In a study of Houston's Hurricane Harvey, Blacks and the unemployed were much more likely than Whites or the employed to have PTSD. 56 A study of New Orleans' Hurricane Katrina found a legacy of damaged infrastructure throughout the city, 15 years after the disaster, 57 while a review of UK floods found infrastructure deterioration was a primary driver of urban flood risk. 58 Flood preparedness was also prioritized in one review, 59 while a study of Hurricane Harvey found those who took preparedness measures fared better in the storm-associated flooding.…”
Section: New Health and Flooding Research In 2020mentioning
confidence: 99%